RIO+10 RESULTS - Diniz, Eliezer Martins (Revista do Departamento de Geografia, 2011)
The World’s Committee on Sustainable Development (WCSD) called Rio+10, took place in Johannesburg (South Africa) in 2002and succeeded  the United Nations Conference on Environment and Development (UNCED), or Rio92,  and  the United Nations Conference onHuman Environment (UNCHE) held in Stockholm in 1972. The relevance of the Johannesburg event is related to mankind’s urgent need to come to an agreement about the level of acceptable anthropic interference in the world’s environment.  This text aims to report Rio+10main decisions using the official documents of the event as a source and evaluate the evolution and the coherence regarding to theprevious conferences. The author also discusses the commitments taken and demonstrates  some implications for the Brazilian case.